Sprayable microemulsion of diphenhydramine hydrochloride for dermal delivery - Arpa, Muhammet Davut; Arslan, Tuğba; Eraslan, Huriye; Üstündağ Okur, Neslihan (My University, 2024)
In this work, a sprayable microemulsion of diphenhydramine hydrochloride (DPH HCl) was developed for use in conditions that cause itching, such as insect bites, mild sunburns, and skin irritations. Microemulsions were prepared using oleic acid and isopropyl myristate as the oil phase (1:2), Tween 20 and Transcutol HP as surfactants, isopropyl alcohol as co-surfactant, and water. The microemulsions (M1, M2, and M3) that presented greater area were selected as lead microemulsions and loaded with 2% DPH HCl (w/w). The physical stabilities of drug-loaded formulations with a droplet size of 15.998-19.030 nm, polydispersity index of 0.404-0.516, and turbidity of 2.41-2.50 Ntu were evaluated as appropriate. The microemulsions showed a great spread area in sprayability studies. Moreover, DPH HCl release from microemulsions reached 80-100% within one hour. The sprayable microemulsions were highly suitable for topical application of DPH HCl and can be evaluated for clinical applications with further studies.
Keywords: Dermal Delivery; Diphenhydramine Hydrochloride; Microemulsion; Topical Application; Topical Spray